Anti-hyperglycemic and antioxidant effect of fucoidan extract from Lessonia trabeculata in alloxan-induced diabetes rats - Loayza-Gutiérrez, Lillyan Teresa; Apumayta-Suárez, Eder Valdir; Abdala-Díaz, Roberto Teófilo; Aguilar-Mendoza, Luis Ángel; Chávez-Pérez, Jorge Antonio; Decara, Juan (Springer, 2022)
The objective of this research was to evaluate a nutritional strategy based on the consumption of a fucoidan extract from brown algae Lessonia trabeculata to control oxidative stress in experimental alloxan-induced insulin-dependent diabetes mellitus rats. Over 30 days, 75, 100, and 125 mg kg−1 of body weight of fucoidan doses were administered and both positive and negative control (n = 5 per group). Serum, liver, pancreas, and kidney biochemical indicators of oxidative stress improvement were evaluated. Measures included lipid peroxidation, superoxide dismutase and catalase activity, and antioxidant activity by assessment of free radical scavenging power and histopathological changes. The results showed an increase in the activity of antioxidant enzymes while reducing oxidative damage (lipid peroxidation index) in serum (p ≤ 0.05) and tissues (p ≤ 0.05). Further, no liver necrosis was observed in treated groups, unlike the Type 1 diabetes positive control group that presented mild necrosis and moderate congestion. In the pancreas, treated rats presented mild oedema, while the positive control group showed moderate oedema. A significant protective effect against oxidative stress caused by alloxan-induced diabetes was found in this model, therefore it can be concluded that fucoidan extracted from the Lessonia trabeculata algae could be considered a good functional compound for the control of oxidative stress in diabetic patients. Because diabetes is such a widespread public health issue, developing fucoidan-based products could be a natural way to improve patients' quality of life.
Keywords: Reconstrución; Functional data; Partially observed data; Reconstruction; Depth measures